Laura Endress, Les trajectoires textuelles de l’Hercule médiéval : de la mythographie à l’historiographie et au-delà. Avec édition critique partielle du livre IX de l’Ovide moralisé - Laura Endress (Perspectives Médiévales, 2023)
This thesis aims to shed new light on the myth of Hercules in medieval texts, by studying its sources and evolution. A particular focus is on little-studied, partially unedited textual material from 12th to 15th century France. Texts examined include, on the one hand, Latin commentaries on the Classics – on the Metamorphoses in particular – and related mythographic treatises, and, on the other, vernacular historiographical compilations, which evolved in close relation to works of historical romance. On the basis of texts belonging to these distinct traditions, it is possible to consider a large array of Hercules-related materials integrated within different interpretative contexts, to study the evolution of various episodes of the hero’s life within and across textual traditions and to identify intersections between them. A third focus is on the sources and manuscript tradition of the Ovide moralisé, a 14th century French adaptation of Ovid’s Metamorphoses, situated at the crossroads of different traditions, which completes the Ovidian narrative with material from a variety of sources. The study of Hercules’ life in the Ovide moralisé attempts to elucidate possible sources of specific episodes that innovate with regard to the Metamorphoses, and to offer new insights into the complex manuscript tradition of the work. This study is accompanied by a provisional critical edition of the life of Hercules in book IX of the Ovide moralisé (lines 1-1036).